EFEKTIVITAS PENDEKATAN PROJECT BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN VOKASIONAL MEMBUAT EKOBRIK BAGI ANAK TUNAGRAHITA RINGAN - dermawan, anggie kurnia (RC-INSTITUT, 2019)
This research is motivated by problems found in the field where at present there is a lot of plastic waste and plastic bottles that are just wasted and pollute the environment such as on the beach, at sea, and in rivers. Solutions to reduce plastic waste and plastic bottles that is by recycling by making a skill called ecobrics that is making a simple and unique bench. Then the background of this research is also the problems found in Perwari Padang SLB, namely there are five mild retarded students in class XII who experience problems in learning skills. When learning the skills of the five mentally retarded students, they seemed to be less interested when learning the skills, which caused students to get bored easily. Based on these problems, researchers are interested in trying out a project based learning approach to making ecobric vocational skills. This type of research is pre-experimental with the type of design one group pretest and posttest. Where the subject consisted of five mild mental retardation students, beginning with a pretest, then given treatment or finally given a posttest. The pretest and posttest scores were processed and compared using the Mann Whitney test which resulted in Uhit = 25 and Utab = 2 at a significant level of 95 % and ? = 0.05. The alternative hypothesis is accepted because Uhit>Utab, this proves that the project based learning approach is effectively used in making ecobric skills for mild retarded children in Perwari Padang SLB.